1997
DOI: 10.1152/ajpcell.1997.273.3.c973
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific expression of P2Y receptors, ecto-apyrase, and ecto-5'-nucleotidase in myeloid leukocytes

Abstract: The expression of P2 purinergic receptor subtypes in leukocytes varies with both lineage and developmental stage. Given the recent identification and cloning of at least seven distinct G protein-coupled ATP receptor subtypes (P2Y family), we investigated P2Y receptor subtype expression during myeloid cell differentiation. We observed that KG-1 myeloblasts express P2Y1 but not P2Y2 receptors (previously termed P2U receptors), whereas later myeloid progenitors, including HL-60 promyelocytes and THP-1 monocytes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 11 publications
5
53
1
Order By: Relevance
“…Although leukocytes can also use ATP as a signaling molecule (33,39,40), it is not clear whether ATP is used in the leukocyte response in the meninges. The meninges are an important site for infections by viruses and bacteria so understanding this response will be important.…”
Section: Discussionmentioning
confidence: 99%
“…Although leukocytes can also use ATP as a signaling molecule (33,39,40), it is not clear whether ATP is used in the leukocyte response in the meninges. The meninges are an important site for infections by viruses and bacteria so understanding this response will be important.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, original studies suggested that CD73 promoter constructs lacking the consensus CRE were still functional and that CD73 production in myeloid cell lines was not influenced by agents that elevate intracellular cAMP (12). It has been reported, however, that agents that activate protein kinase C (i.e., PMA) strongly induce CD73 mRNA and activity in myeloid leukocytes (HL-60 cells) (24). Similarly, in Jurkat T cells, PMA induces CD73 gel shift using oligonucleotides corresponding to the CRE site (25).…”
Section: Discussionmentioning
confidence: 99%
“…This is an important consideration because ecto-nucleotidases will rapidly degrade this ATP and thus minimize the maintenance of high extracellular ATP concentrations in the local vicinity of the macrophage. Indeed, we have recently characterized the expression of both the CD39 ectoATPase and the CD73 ecto-5Ј nucleotidase in human monocyte/ macrophage cell types [42]. The recent discovery that ICE/ caspase-1 also processes IFN-␥-inducing factor (IGIF or IL-18) to its active form raises an additional possibility that T cell-mediated IFN-␥ production can also be indirectly regulated by ATP-activated macrophages [43].…”
Section: Discussionmentioning
confidence: 99%